Pengembangan Aplikasi Radio Digital dan Obat Herbal BSK Media - Agata Suryonugroho, Paulus; Guslinar Perdana, Erda (eProceedings of Applied Science, 2023)
Abstract—BSK Media is a radio home for several nearby radio stations and provides on air and off air content. BSK Media previously had a website, but the site did not run well because the system did not work well and there was no herbal medicine sales segment sold by BSK Media. Therefore, the author designed an android-based application with existing features, namely the radio play feature, sales of herbal medicines carried out by BSK Media, as well as providing news information to users and applications that will be used by admins to manage data through mobile applications. It is hoped that with this application, users can listen to streaming radio from various places and get herbal medicines from BSK Media products, and BSK Media can manage data related to input data. This application is tested using black box testing. The purpose of the test is to find out the application is running as expected.Keywords: Herbal Medicine, Digital Radio, Android